2014
DOI: 10.17221/9/2013-pps
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antifungal activity of sodium salts against onion basal rot caused by Fusarium oxysporum f.sp. cepae

Abstract: Türkkan M., Erper I. (2014): Evaluation of antifungal activity of sodium salts against onion basal rot caused by Fusarium oxysporum f.sp. cepae. Plant Protect. Sci., 50: 19-25.The efficacy of twelve sodium salts as possible alternatives to synthetic fungicides for the control of onion basal rot caused by Fusarium oxysporum f.sp. cepae was evaluated. In vitro tests showed that there were significant differences between the inhibitory effects of sodium salts on the mycelial growth (P ≤ 0.05) and 2% (w/v) concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…The results in Table (3) show that pH 3 and 9 slightly controlled the incidence of green and blue molds on orange fruits by 20.83 % and 29.17 % and by 25.0 % and 37.5 %, respectively, and basic pH value was more effective than acidic pH. These findings are in agreement with other previous studies (Eckert and Eaks, 1989;Pitt and Hocking, 1997;Smilanick et al, 2005Smilanick et al, , 2006Smilanick et al, and 2008Guo et al, 2014;Turkkan andErper, 2014 andGhadimipour andSedigh-Eteghad, 2015).…”
Section: In Vivo Studies Effect Of Ph On Green and Blue Mold Diseasessupporting
confidence: 90%
See 1 more Smart Citation
“…The results in Table (3) show that pH 3 and 9 slightly controlled the incidence of green and blue molds on orange fruits by 20.83 % and 29.17 % and by 25.0 % and 37.5 %, respectively, and basic pH value was more effective than acidic pH. These findings are in agreement with other previous studies (Eckert and Eaks, 1989;Pitt and Hocking, 1997;Smilanick et al, 2005Smilanick et al, , 2006Smilanick et al, and 2008Guo et al, 2014;Turkkan andErper, 2014 andGhadimipour andSedigh-Eteghad, 2015).…”
Section: In Vivo Studies Effect Of Ph On Green and Blue Mold Diseasessupporting
confidence: 90%
“…A study was conducted to estimate the fungicidal activity of the tested fungicides and antioxidant either separately under defined pH values or in mixtures under native pH medium. The effect of pH on mycelial growth of fungi was examined by adjusting (PDA) at 3.0 to 11.0 using 1.0 N NaOH or HCl prior to autoclaving, the degree of pH was determined by the pH meter (Turkkan and Erper, 2014). The fungicides were diluted in sterile distilled water, then added to cooled PDA medium at concentrations of 0.001, 0.005, 0.01, 0.05, 0.1, 0.5, 1.0, 2.5, 5.0 and 10.0 µg a.i.…”
Section: In Vitro Fungitoxicity Testmentioning
confidence: 99%
“…Although the use of chemical fungicides is a common control measure against box blight in ornamental situations, the potential effects of these treatments on the wider environment and human health make it necessary to find alternative strategies for disease management (LaMondia, ). The use of natural compounds such as organic and inorganic chemicals with low mammalian toxicity may be one of the better alternatives for disease control in natural environments (Olivier et al., ; Turkkan & Erper, ). However, before attempting to assess the efficiency of such compounds against boxwood blight in the forest, preliminary in‐vitro tests are required to evaluate their activities against both growth and spore germination of C. pseudonaviculata .…”
Section: Discussionmentioning
confidence: 99%
“…Biorational fungicides are active at low concentrations, have little or no adverse consequences for the environment and nontarget organisms, but are either lethal or suppressive to target fungi (Diver & Hinman, ; Horowitz, Ellsworth, & Ishaaya, ). Their fungicidal and fungistatic effects have been demonstrated on several fungal plant pathogens such as Botrytis cinerea (Mills, Platt, & Hurta, ; Zaker, ), Helminthosporium solani (Olivier, Halseth, Mizubuti, & Loria, ), Fusarium oxysporum (Arslan, Kadir, Vardar, & Karabulut, ; Elmer, ; Turkkan & Erper, ; Zaker, ), Alternaria alternata (Mills et al., ; Zaker, ), Rhizoctonia solani and Sclerotinia sclerotiorum (Arslan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with Dionisio and Koabyashi (2004) who found that organic and inorganic salts, that is, Na 2 CO 3 (4 g/L), NaClO (5 g/L), NaHCO 3 , CaCl 2 , and NaCl (6 g/L) completely inhibited spore germination of fungi causing crown rot diseases in banana, that is, L. theobromae, Thielaviopsis paradoxa, C. musae, C. gloeosporioides, Fusarium verticillioides, and Fusarium oxysporum. Turkkan and Erper (2014) found that sodium metabisulfite completely inhibited mycelial growth of F. oxysporum.f.sp.capae, the cause of onion basal rot.…”
Section: Screening Of Salts Against Causal Organismsmentioning
confidence: 96%